Association between Food Specific IgG Antibodies with Clinical Activity of Disease in Patients with Inflammatory Bowel Disease - Parhusip, Santi Sumihar Rumondang; Rengganis, Iris; Simadibrata, Marcellus; Abdullah, Murdani; Shatri, Hamzah; Yunihastuti, Evy; Wibowo, Heri (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Background: Inflammatory bowel disease (IBD) is an autoimmune disease that is influenced by food, an important factor in accelerating its clinical disease activity because of intestinal inflammation trough formation of antigen-antibody complex. Food-specific IgG examination can identify the types of person foods consumes that are maybe responsible for disease activity. It is useful in treating IBD without risking malnourishment as it is tailored to the individual immune profile.Method: This is a cross-sectional study involving 113 patients diagnosed with IBD by colonoscopy. Examination of serum IgG specific for 220 types of foods was performed using ELISA and immuno-array techniques. Disease clinical activity was assessed using the Mayo index and Crohn's disease activity index.Results: The highest proportion of dietary IgG in Crohn's disease was peas (100%), barley (97.9%), eggs (95.9%), milk (81.6%), and corn (75.5%); while in ulcerative colitis it was barley (98.4%), peas (96.8%), egg whites (92.2%), corn (82.8%), and prunes (78.1%). In ulcerative colitis, there was a weak negative correlation between cashew nuts IgG (r = -0.347; p = 0.041) and chickpeas IgG (r = -0.473; p = 0.017) with clinical disease activity; while in Crohn's disease, a weak positive correlation with disease activity was seen in barley (r = 0.261; p = 0.042).Conclusion: There was a weak negative correlation between cashew and chickpea-specific IgG antibodies with clinical activity of ulcerative colitis, and a weak positive correlation between barley-specific IgG antibodies and Crohn's disease clinical activity.